Experimental investigation on compression ignition engine powered with pentanol and thevetia peruviana methyl ester under reactivity controlled compression ignition mode of operation. (June 2021) - Harari, P.A.; Banapurmath, N.R.; Yaliwal, V.S.; Soudagar, Manzoore Elahi M.; Khan, T.M. Yunus; Mujtaba, M.A.; Safaei, Mohammad Reza; Akram, Naveed; Goodarzi, Marjan; Elfasakhany, Ashraf; EL-Seesy, Ahmed I.
Abstract: In the current study, an effort is carried out to study the influence of pentanol as low reactive fuel (LRF) along with diesel and Thevetia peruviana methyl ester (TPME) as high reactive fuels (HRF) in reactivity controlled compression ignition (RCCI) engine. The experiments are conducted on dual fuel engine at 50% load for RCCI mode of operation by varying pentanol percentage in injected fuels. The results revealed that RCCI mode of operation at 10% of pentanol in injected fuels exhibited higher brake thermal efficiency (BTE) of 22.15% for diesel and pentanol fuel combination, which is about 9.1% and 27.3% higher than other B20 and pentanol, B100 and pentanol fuel combinations respectively. As the percentage of pentanol increased in injected fuels, hydrocarbon (HC) and carbon monoxide (CO) emissions are increased while nitrogen oxide (NOx ) and smoke emissions are decreased. Among various fuel combinations tested diesel and pentanol fuel combination gives lower HC, CO and smoke emissions and higher NOx emissions. At 10% pentanol in injected fuels, the highest heat release rate (HRR) and in-cylinder pressure are found for diesel and pentanol fuel combinations compared with other fuels.